Lanthanum based high surface area perovskite-type oxide and application in CO and propane combustion - da Silva, Paulo Roberto Nagipe; Soares, Ana Brígida (Eclética Química, 2009)
The perovskite-type oxides using transition metals present a promising potential as catalysts in total oxidation reaction. The present work investigates the effect of synthesis by oxidant co-precipitation on the catalytic activity of perovskite-type oxides LaBO3 (B= Co, Ni, Mn) in total oxidation of propane and CO. The perovskite-type oxides were characterized by means of X-ray diffraction, nitrogen adsorption (BET method), thermo gravimetric and differential thermal analysis (ATG-DTA) and X-ray photoelectron spectroscopy (XPS). Through a method involving the oxidant co-precipitation it’s possible to obtain catalysts with different BET surface areas, of 33-44 m2/g, according the salts of metal used. The characterization results proved that catalysts have a perovskite phase as well as lanthanum oxide, except LaMnO3, that presents a cationic vacancies and generation for known oxygen excess. The results of catalytic test showed that all oxides have a specific catalytic activity for total oxidation of CO and propane even though the temperatures for total conversion change for each transition metal and substance to be oxidized.